2023
DOI: 10.3390/antibiotics12061062
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Antibiotic Resistance and Virulence Factors in Environmental Isolates of Vibrio Species

Abstract: The outbreak of waterborne diseases such as cholera and non-cholera (vibriosis) is continuously increasing in the environment due to fecal and sewage discharge in water sources. Cholera and vibriosis are caused by different species of Vibrio genus which are responsible for acute diarrheal disease and soft tissue damage. Although incidences of cholera and vibriosis have been reported from the Vaishali district of Bihar, India, clinical or environmental strains have not been characterized in this region. Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Additionally, significant increases in bacterial resistance to various antibiotics have been observed in fish farms attributed to the excessive use, incorrect prescription and/or over-prescription of antibiotics [3]. For instance, Pandey et al reported the resistance of Vibrio species (Vibrio proteolyticus, V. campbellii, V. nereis, V. cincinnatiensis, and V. harveyi) to antibiotics ampicillin and cephalexin [4]. Adah et al reported multiple antibiotic resistance index values between 0.20 and 0.80 from Aeromonas strains (Aeromonas caviae, A. veronii, A. hydrophila, A. dhakensis and A. enteropelogenes) isolated from Clarias gariepinus (40.9% isolated from diseased fish, Fishes 2024, 9, 99 2 of 19 and 25% from healthy fish) acquired from farms that intensively utilized antibiotics [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, significant increases in bacterial resistance to various antibiotics have been observed in fish farms attributed to the excessive use, incorrect prescription and/or over-prescription of antibiotics [3]. For instance, Pandey et al reported the resistance of Vibrio species (Vibrio proteolyticus, V. campbellii, V. nereis, V. cincinnatiensis, and V. harveyi) to antibiotics ampicillin and cephalexin [4]. Adah et al reported multiple antibiotic resistance index values between 0.20 and 0.80 from Aeromonas strains (Aeromonas caviae, A. veronii, A. hydrophila, A. dhakensis and A. enteropelogenes) isolated from Clarias gariepinus (40.9% isolated from diseased fish, Fishes 2024, 9, 99 2 of 19 and 25% from healthy fish) acquired from farms that intensively utilized antibiotics [5].…”
Section: Introductionmentioning
confidence: 99%